2018
DOI: 10.5414/alx01503e
|View full text |Cite
|
Sign up to set email alerts
|

Workplace exposure to wood dust and the prevalence of wood-specific sensitization

Abstract: Wood is processed worldwide, and occupational exposure to wood dust is affecting millions of workers. Studies have identified wood dust as a risk factor for non-malignant respiratory diseases consistent with both an allergic and a non-allergic origin. This paper summarizes our current knowledge on the importance of specific sensitization among subjects occupationally exposed to wood dust. Specific sensitization to wood dust exists, but is probably of minor importance for most wood species. In order to move the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…According to some authors, wood dust is more dangerous that formaldehyde [29]. Occupational exposure to wood dust affects 3.6 million workers within the European Union (EU) [30].…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors, wood dust is more dangerous that formaldehyde [29]. Occupational exposure to wood dust affects 3.6 million workers within the European Union (EU) [30].…”
Section: Introductionmentioning
confidence: 99%
“…hypersensitivity pneumonitis and occupational asthma. Moreover, many hard and softwoods contain chemicals that can irritate the eyes, nose, and throat causing shortness of breath, dryness, and soreness of the throat, sneezing, tearing, and rhinitis (Schlünssen et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although specific immunoglobulin E (IgE) sensitization has been reported in woodworkers, Type 1 allergy is not considered to be a major factor. It is estimated that only 20% of patients working in the wood industry referred for clinical evaluation demonstrate sensitization [4]. Kespohl et al [29] demonstrated that exposure to wood dust can also induce irritative as well as allergic respiratory disease and that the prevalence of sensitization is much higher for tropical (30%) than nontropical wood species (3%).…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%